A proposal to modify the moment coefficient in Eurocode 2 for predicting the residual strength of corroded reinforced concrete beams. (15th August 2019) - O'Flaherty, Fin; Browne, Elena
Highlights: EC 2 analysis for predicting the strength of deteriorated reinforced concrete beams. Strength related to the degree of under-reinforcement and corrosion of the steel. Modified moment coefficient ( K corr ) is used to calculate the reduced moment ( M corr ). Guidance provided to determine M corr for actual in-situ reinforced concrete beams. Analysis applied to concrete with grades both greater and less than C35/45. Abstract: Ultimate limit state (ULS) criteria are used to design reinforced concrete beams which give a ductile behaviour at failure. This means the resisting moment, M t, is less than the resisting moment in compression, M c . Since steel reinforcement is susceptible to corrosion, the ultimate capacity can be seriously affected as the degree of corrosion increases. The impact of corrosion to the main steel reinforcement on the flexural performance of reinforced concrete beams is investigated. Beams measuring 100 mm wide × 150 mm deep with differing levels of under-reinforcement ( M t / M c ratios) were tested under four-point bending. Although the design code for reinforced concrete beam design has gone through various changes over the years, the fundamentals for design has broadly remained the same in that the beam is designed with an ultimate moment-coefficient ( K = M / f c b d 2 ) with sufficient capacity to be able to easily carry the service loads it is exposed to. However, the long term influence of corrosion on the steel reinforcement is not considered at the design stage although a manufacturing factor of safety is applied. The analysis in this paper uses a modified-moment coefficient ( K corr = M corr / f ck b d 2 ) based on EC 2 ultimate limit state design guidelines to predict the residual flexural strength of reinforced concrete beams suffering from main steel corrosion. Two grades of concrete (>C35/45 and <C35/45) are considered as used in EC 2 [1]. The results obtained in this investigation show that there is a relationship between the reducing moment-coefficient of corrosion-affected concrete beams and both the degree of under-reinforcement ( M t / M c ) and degree of corrosion to the main steel reinforcement for beams with concrete grades >C35/45. The analysis is then extended to include test data from other researchers to develop a similar simplified empirical analytical expression for beams with concrete grades <C35/45, thereby enabling a prediction of residual strength due to corrosion to be made for any beam size or concrete strength grade.